The Role of the Community and Village Empowerment Office in Improving the Development Village Index - febriani, fika; Paisal Topan Nugraha; Ida Noviyanti; Ikhtia Faizatuz Zahrah; Dio Alip Fadilla; Regi Refian Garis (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
This research aims to understand the role of the Ciamis Regency Community and Village Empowerment Service (DPMD) in increasing the Village Development Index (IDM). IDM is an indicator that reflects village progress in social, economic and ecological aspects. Using a qualitative approach, this research explores various programs and policies implemented by DPMD, as well as the factors that influence their success. The research results show that the Ciamis Regency DPMD has succeeded in increasing village status to "Independent" in 2024, with the number of independent villages reaching 210, a significant increase compared to previous years. This success is supported by the commitment of the local government, adequate budget allocation, strong capacity of village officials, and the availability of quality village data. Community empowerment programs, development of village officials, and facilitating access to village resources and funding are the keys to this achievement. However, this research also found several challenges that still need to be faced, such as limited infrastructure, limited access to capital, and coordination between agencies that needs to be strengthened. To overcome these obstacles, the Ciamis Regency DPMD has implemented various strategies, including strengthening the capacity of village officials, improving the quality of village data, developing the village economy, and increasing access to public services. In conclusion, with strong commitment and continuous efforts, the Ciamis Regency DPMD is optimistic that it can continue to improve the welfare of village communities and achieve independent village status throughout its region, making a significant contribution to sustainable development in Indonesia.